Investigating the sexual quality of life and its relationship with general health in older men in Iran - Alireza Najimi; Yousef Veisani; Sanaz Azami; Arman Azadi (Wolters Kluwer Medknow Publications, 2020)
INTRODUCTION: Sexual problems in elder people are considered as a public health concern and can affect their overall health and quality of life. This study aimed to investigate the sexual quality of life and its relationship with general health in older men in the west of Iran. METHODS: This was a cross-sectional study among 362 older men aged 60 years or older attending Comprehensive Health Care Centers in Ilam, Iran. Samples selected through Quota sampling method and simple random sampling. Data were collected using the Sexual Quality of Life Questionnaire-Male and General Health Questionnaire-28. RESULTS: The mean ± standard deviation (SD) of age was 69.9 ± 8.1 years. The mean ± SD score of sexual quality of life and general health of older men was 46.6 ± 14.6 and 19.2 ± 9.7, respectively. A positive and significant association was found between sexual quality of life and general health (P < 0.001, r = −0.41). Moreover, general health, age, sleep problems, and the level of education were the important predictors for sexual quality of life in elder men (P < 0.05). CONCLUSION: According to the results, the sexual quality of life of participants was at a moderate level. Since only some factors influencing the sexual quality of life were ascertained, further studies are required to investigate all factors influencing older men's sexual quality of life.